2016
DOI: 10.11648/j.ijaas.20160201.12
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Salt Tolerant Gene (<i>TaNIP</i>) and Its Expression in Three Selected Wheat Genotypes Through Plant Breeding Programs Under Salinity Conditions

Abstract: Abstract:High soil salinity is a major abiotic stress in plant production worldwide. TaNIP gene was identified and cloned through the gene chip expression analysis of a salt-tolerant wheat mutant RH8706-49 under salt stress. Quantitative reverse transcription -PCR (Q-RT-PCR) was used to detect TaNIP salt tolerant gene and its expression in some selected wheat genotype for salt tolerance through plant breeding programs. The results of qualitative PCR Reaction-cDNA and Quantitative Real-Time PCR showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In the previous study, Al-Mishhadani et al (2) showed that the TaNIP gene found only in these selected genotypes with length of 189 bp, while this gene absent in salt sensitive cultivar (Iraq) and gave high gene expression at high salinity level (16 ds/m). Therefore, according to these results, these genotypes are considered as a high salt tolerant genotypes, which improved through plant breeding programs genotypes, this conclusion is agreed with the previous studies, which they reported that there is a strong development in salt tolerance obtained in these selected genotypes through plant breeding program (2,5,7,8). Under high salinity condition, the selected genotypes were more salt tolerance than the local cultivars, may be due to they contained high organic compounds in their upper leaves (Table 2).…”
Section: Organic Compoundmentioning
confidence: 87%
See 2 more Smart Citations
“…In the previous study, Al-Mishhadani et al (2) showed that the TaNIP gene found only in these selected genotypes with length of 189 bp, while this gene absent in salt sensitive cultivar (Iraq) and gave high gene expression at high salinity level (16 ds/m). Therefore, according to these results, these genotypes are considered as a high salt tolerant genotypes, which improved through plant breeding programs genotypes, this conclusion is agreed with the previous studies, which they reported that there is a strong development in salt tolerance obtained in these selected genotypes through plant breeding program (2,5,7,8). Under high salinity condition, the selected genotypes were more salt tolerance than the local cultivars, may be due to they contained high organic compounds in their upper leaves (Table 2).…”
Section: Organic Compoundmentioning
confidence: 87%
“…Increasing salt tolerance in plant requires new genetic source of this character powerful and molecular techniques for detecting salt tolerance genes in new material useful for determining the salt tolerance degree. Salt tolerance in plant depends on physiological mechanisms controlled by genes which gave expression under salinity conditions (2,5). Plants have evolved several salt tolerance mechanisms to reduce the adverse effect of salinity (16), this mean that there are different genes for controlling these mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Munns et al (2012) reported that HKT1 gene encoding to Na + -selective transporter in durum wheat, by exclusion of Na+ from root xylem vessels to leaf sheaths, reducing shoot accumulation. Biotechnology techniques are advanced using in plants to support the diagnostic purpose like DNA microarray (Kawaura et al, 2006), northern blot (Rahaie et al, 2011) and real time PCR (Al-Mashhadani et al, 2016) technologies have been employed to study expression profiles in wheat and other plant species. TaqMan real time PCR is one of molecular techniques using to detect or determine the genes expression.…”
Section: A R T I C L E I N F O Abstract Article Historymentioning
confidence: 99%